Off the Map? Sonic Art in the New Media Landscape - Hyde, Joseph (Circuit, 2003)
This article examines the place of Sonic Art in the current cultural landscape. It deconstructs some of the preconceptions often associated with this field, and postulates that because work of this nature does not necessarily fit commonly recognised categories and hierarchies, it becomes effectively invisible (and therefore inaudible). While not attempting to propose a solution, the article looks at various pointers towards an alternative cultural 'placing' of sonic art; along the way looking at other genres such as hip-hop, techno and electronica, and the dichotomies of so-called 'high' and low' culture, media convergence and divergence and cultural homogenisation and fragmentation.